Catalyzing action on HIV/SRH integration: lessons from Kenya, Malawi, and Zimbabwe to spur investment. Issue 1 (31st December 2022) - Fleischman, Janet; Kachale, Fannie; Mhuriro, Fatima; Mugambi, Mary; Ncube, Getrude; Ndwiga, Albert; Nyirenda, Rose; Carter, Anna; Rodrigues, Jessica; Segal, Kate
ABSTRACT: The HIV pandemic has long revealed the inequities and fault lines in societies, one of the most tenacious being the pandemic's disproportionate impact on adolescent girls and young women. In east and southern Africa, renewed global action is needed to invigorate an effective yet undervalued approach to expanding HIV prevention and improving women's health: integration of quality HIV and sexual and reproductive health (SRH) services. The urgency of advancing effective integration of these services has never been clearer or more pressing. In this piece, national health officials from Kenya, Malawi, and Zimbabwe and global health professionals have joined together in a call to catalyze actions by development partners in support of national strategies to integrate HIV and SRH information and services. This agenda is especially vital now because these adolescent girls and young women are falling through the cracks due to the cascading effects of COVID-19 and disruptions in both SRH and HIV services. In addition, the scale-up of pre-exposure prophylaxis (PrEP) has been anemic for this population. Examining the opportunities and challenges of HIV/SRH integration implemented recently in three countries – Kenya, Malawi, and Zimbabwe – provides lessons to spur integration and investments there and in other nations in the region, aimed at improving health outcomes for adolescent girls and young women and curbing the global HIV epidemic. While gaps remain between strong national integration policies and program implementation, the experiences of these countries show opportunities for expanded, quality integration. This commentary draws on a longer comparative analysis of findings from rapid landscaping analyses in Kenya, Malawi, and Zimbabwe, which highlighted cross-country trends and context-specific realities around HIV/SRH integration.